If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 1 = 26 Reorder the terms: 1 + 5m = 26 Solving 1 + 5m = 26 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5m = 26 + -1 Combine like terms: 1 + -1 = 0 0 + 5m = 26 + -1 5m = 26 + -1 Combine like terms: 26 + -1 = 25 5m = 25 Divide each side by '5'. m = 5 Simplifying m = 5
| 0.04x+0.07*(15000-x)=600 | | 5a+5=7+2a | | -1-2-4= | | 8x-9y=3 | | 8x+7=7x | | 2s+2(s+2)=4(s+2)-4 | | x+(-17)=1 | | x*(x+1)/2=453 | | -2y=-8x | | (1/4)-(5/y)=3 | | 7y+4(y-6)=4(y+2)-5 | | p(x)=3x^4-4x^3+x^2+6x-2 | | -2d+8=2(-d+4) | | 3.6x+14.7=.3-1.2x | | .3x+8.6=.65x+10 | | 13-20-(-2)= | | y=-4x^5+2x^4+6x+5 | | 25-2(7+5)= | | 36+35/5*4 | | 4(c-3)-6=6 | | -7(x+2)-18=25+6 | | 141/9-13/18 | | .4+.6x=.53+.5x+1.5 | | 3x^4-4x^3+x^2+6x-2= | | 2x+y=-400 | | -(1-2)-4= | | y=-3x^9+8x^6+7x^5+7 | | w=p(v-l) | | 8-(11-7)= | | 5/9+10 | | (4w-9)(5-w)=0 | | 9-3(-2-5)=30 |